2014
DOI: 10.1371/journal.pone.0100785
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Retinopathy of Prematurity in Premature Neonates with a Birth Weight below 1500 Grams and a Gestational Age Less than 32 Weeks: A Study from a Tertiary Care Hospital in a Lower-Middle Income Country…

Abstract: IntroductionRetinopathy of prematurity (ROP) is a treatable cause of blindness in neonates. In Pakistan, ROP is often not recognized early because screening and treatment programs are not yet in place in most neonatal units, even in tertiary care hospitals. It is hoped that this report will help inform medical professionals of the magnitude of the problem and help to design appropriate management strategies.ObjectivesThe aim was to determine the frequency of ROP in premature and very low birth weight (BW) neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 10 publications
1
14
2
Order By: Relevance
“…In our study the incidence of ROP was 4.4%. It is lower to the incidence reported in a study from Aga Khan University Hospital Pakistan,2 but very different from the studied in developed countries 3. This variation might be partly accounted by differences in the proportions of infants at high risk of ROP who survive when born at an early GA 2.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In our study the incidence of ROP was 4.4%. It is lower to the incidence reported in a study from Aga Khan University Hospital Pakistan,2 but very different from the studied in developed countries 3. This variation might be partly accounted by differences in the proportions of infants at high risk of ROP who survive when born at an early GA 2.…”
Section: Discussioncontrasting
confidence: 66%
“…Advances in neonatal intensive care management of extremely premature infants in the developed world and now also in developing countries, has led to an increased survival and an increase risk of long term morbidities like retinopathy of prematurity (ROP) 1. There are differing trends in the frequency and severity of ROP ranging from 10.5% to as high as 58% 2,3. In preterm neonates the development of any ROP is associated with both lower birth weight (BW) and lower gestational age (GA) 4.…”
Section: Introductionmentioning
confidence: 99%
“…In VP group, the most prevalent and the least comorbidities were NDD (73.0%, 95%CI:57.0-0.85) and NEC (0.0), respectively (21,22). Table 4 (10,(27)(28)(29)(30)(31)(32). The univariate and multiple-regression analysis were not possible in VP newborns because of the studies limitations.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of ROP in Pakistan is not known as multi-center large prospective population-based studies had never been conducted. However, some studies from Pakistan reported the frequency of ROP is ranging from 10.5% [11] to 32.4% [12].…”
Section: Introductionmentioning
confidence: 99%